2006
DOI: 10.1007/s11104-005-5446-7
|View full text |Cite
|
Sign up to set email alerts
|

Response of Litter Decomposition to Simulated N Deposition in Disturbed, Rehabilitated and Mature Forests in Subtropical China

Abstract: The response of decomposition of litter for the dominant tree species in disturbed (pine), rehabilitated (pine and broadleaf mixed) and mature (monsoon evergreen broadleaf) forests in subtropical China to simulated N deposition was studied to address the following hypothesis: (1) litter decomposition is faster in mature forest (high soil N availability) than in rehabilitated/disturbed forests (low soil N availability); (2) litter decomposition is stimulated by N addition in rehabilitated and disturbed forests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
210
3
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 219 publications
(243 citation statements)
references
References 64 publications
(97 reference statements)
18
210
3
7
Order By: Relevance
“…The rehabilitated forest originated as a pine plantation in 1930's that was naturally invaded and colonized by regional broadleaf species from animal and wind dispersal. However, it has yet to recover fully to its pre-disturbance condition over the past several decades (Mo et al, 2003(Mo et al, , 2004(Mo et al, , 2006, creating and maintaining N-limiting conditions (Mo et al, 2006), i.e., N demand by recovering woody vegetation continues to exceed supply of available N. Under N limitation, increasing N commonly decreases biodiversity by enhancing competitive abilities of fast-growing nitrophilous plants with high maximum growth rates, at the expense of slower growing neighbors of smaller stature (Aerts and Chapin, 2000;Gilliam, 2006;Hautier et al, 2009;Bobbink et al, 2010). Because there were no significant increases in understory plant growth in the rehabilitated forest, it is unlikely that competitive exclusion among understory plants contributed to the observed decline of understory cover.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The rehabilitated forest originated as a pine plantation in 1930's that was naturally invaded and colonized by regional broadleaf species from animal and wind dispersal. However, it has yet to recover fully to its pre-disturbance condition over the past several decades (Mo et al, 2003(Mo et al, , 2004(Mo et al, , 2006, creating and maintaining N-limiting conditions (Mo et al, 2006), i.e., N demand by recovering woody vegetation continues to exceed supply of available N. Under N limitation, increasing N commonly decreases biodiversity by enhancing competitive abilities of fast-growing nitrophilous plants with high maximum growth rates, at the expense of slower growing neighbors of smaller stature (Aerts and Chapin, 2000;Gilliam, 2006;Hautier et al, 2009;Bobbink et al, 2010). Because there were no significant increases in understory plant growth in the rehabilitated forest, it is unlikely that competitive exclusion among understory plants contributed to the observed decline of understory cover.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that D. dichotoma, which dominated understory layer in this study, is a highly shade-intolerant species and commonly declines in growth with decreases in light intensity (Takeuchi, 1988). Unlike the rehabilitated forest, the disturbed forest has been constantly subjected to anthropogenic pressure (primarily harvesting of understory vegetation and litter) since time of planting in 1930's and continuing until the late 1990's Mo et al, 1995Mo et al, , 2003Mo et al, , 2006. This type of land use may mitigate effects of N additions, resulting in no significant changes in understory community, and do so for two reasons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations